1999
DOI: 10.1063/1.369563
|View full text |Cite
|
Sign up to set email alerts
|

Effect of twisting on strain tolerance of Bi-2212 multifilamentary round wires

Abstract: Silver sheath Bi2Sr2Ca1Cu2Ox superconducting multifilamentary round wires having various twist pitch lengths and an untwisted one were fabricated by the oxide powder-in-Ag-tube method. The twisting process to a pitch length of 4.5 mm at a diameter of 1.45 mm did not influence the superconducting critical current density Jc whose value was about 90 000 A/cm2 at 4.2 K, 0 T. The Jc of the twisted wires is less sensitive to bending strain as twist pitch length becomes shorter. This phenomenon is explained by the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This model, which accounts for the intrinsic reduction of the effective cross section, cannot explain the presence of a plateau of I c against the twist pitch for large t p values. This is because we have assumed the same local J c values independent of t p and this condition needs to be revised in the light of new experimental findings [21]. The strain tolerance of Bi-2212 multifilamentary round wires improves by twisting the filaments.…”
Section: J C Degradation With the Twist Pitchmentioning
confidence: 99%
See 1 more Smart Citation
“…This model, which accounts for the intrinsic reduction of the effective cross section, cannot explain the presence of a plateau of I c against the twist pitch for large t p values. This is because we have assumed the same local J c values independent of t p and this condition needs to be revised in the light of new experimental findings [21]. The strain tolerance of Bi-2212 multifilamentary round wires improves by twisting the filaments.…”
Section: J C Degradation With the Twist Pitchmentioning
confidence: 99%
“…The strain tolerance of Bi-2212 multifilamentary round wires improves by twisting the filaments. This is ascribed to the increase of the crack resistance of the spiral filaments [21]. Accordingly, the bending strain tolerance is improved for shorter twist pitches and the propagation of cracks is more difficult.…”
Section: J C Degradation With the Twist Pitchmentioning
confidence: 99%
“…This achieves reduction in both of coupling loss of wires and hysteresis loss. It is suggested that multifilaments and strand bundling the wire structure may contribute to an improvement of strain tolerance [9,10]. The strand bundle of wires is considered to be one of a number of means for resolving the challenges listed in figure 1.…”
Section: Introductionmentioning
confidence: 99%